Periostin of human periodontal ligament fibroblasts promotes migration of human mesenchymal stem cell through the αvβ3 integrin/FAK/PI3K/Akt pathway. (20th April 2015) - Matsuzawa, M.; Arai, C.; Nomura, Y.; Murata, T.; Yamakoshi, Y.; Oida, S.; Hanada, N.; Nakamura, Y.
Abstract : Background and Objective: The periodontal ligament (PDL) is characterized by rapid turnover, high remodeling capacity and high inherent regenerative potential compared with other connective tissues. Periostin, which is highly expressed in the fibroblasts in the PDL, has been widely discussed in relation to collagen fibrillogenesis in the PDL. Recently, several reports have indicated periostin in cell migration. The aim of this study was to examine whether human PDL fibroblasts (hPDLFs) with high levels of periostin expression promote the migration of human bone marrow mesenchymal stem cells (hMSCs). Material and Methods: The migration of hMSCs was examined by transwell chamber migration assay under different conditions: medium alone, hPDLFs, human dermal fibroblasts, recombinant periostin, integrin αvβ3 blocking antibody (anti‐CD51/61 antibody) and inhibitors of FAK (PF431396) and PI3K (LY294002). Phosphorylation of FAK and Akt in hMSCs under stimulation of periostin was examined by western blotting. Results: The migration assay revealed that the number of migrated hMSCs by hPDLFs was significantly larger than those by dermal fibroblasts, periostin small interfering RNA hPDLFs and medium alone. Furthermore, recombinant periostin also strongly induced hMSC migration. The addition of anti‐CD51/61 antibody, PF431396 and LY294002 caused a significant reduction in the number of migrated hMSCs respectively. The anti‐CD51/61 antibody inhibited both FAK and Akt phosphorylations under periostin stimulation. PF431396 inhibited both FAK and Akt phosphorylations. LY294002 inhibited only Akt phosphorylation, and FAK phosphorylation was not influenced under periostin stimulation. Conclusion: Periostin expression in hPDLFs promotes the migration of hMSCs through the αvβ3 integrin/FAK/PI3K/Akt pathway in vitro .